Tuberculous Salpingitis: A Case Report - Rajaratnam, Annie (JCDR Research and Publications (P) Limited, 2013)
Tuberculosis (TB) of the genital tract commonly occurs secondary to a primary lesion. The mode of spread is via the lymphatics, the haematogenous route or less commonly by a peritoneal spread. The fallopian tubes are the first targets, followed by the pelvic organs. Isolated cases of TB which occur in a unilateral fallopian tube are rare, particularly with it as a primary site. The aim of this study was to report a rare case of TB of the left fallopian tube in a post menopausal lady with no positive history, clinical or laboratory finding to suggest it to be a secondary focus. As the pre-operative diagnosis was that of a right ovarian neoplasm, the patient underwent staging laparotomy. TB of the left fallopian tube was diagnosed, as there were numerous typical granulomata throughout the fallopian tube.